THE DESIGN AND PROPERTIES OF SPLIT MASTIC ASPHALT MODIFIED WITH CRUMB RUBBER - Abuseta, Ahmad Alhashmi Salam; Setyawan, Ary; Budiarto, Arif (Jurnal Teknik Sipil, 2014)
AbstractÂ Stone Mastic Asphalt, originated from Germany in the 1970s,has superior properties on heavily trafficked roads and industrial applications. Modification of split mastic asphalt with crumb rubber makes asphalt more temperature stable. The objectives of this research are: To design split mastic asphalt modified with crumb rubber mixture, to get the best composition of stone mastic asphalt modified with crumb rubber for rut and fracture resistance, to assess the physical characteristics of split mastic asphalt modified with crumb rubber and compare with unmodified SMA. Stone mastic asphalt was modified with 0%, 2%, 4% and 6% crumb rubber. The Marshal properties were conducted. The result showed that marshal stability, Marshal Quotient, Voids in Mix (VIM) and Voids in mineral aggregate (VMA) decrease with higher crumb rubber modifier. However, Marshal Flow and Void filled with asphalt (VFWA) increase when crumb rubber modifier was increased. Therefore, Crumb rubber could be used as aggregate substitute for flexible stone mastic asphalt at hot and arid region because it is temperature tolerant and can prevent asphalt cracking.Keywords: Crumb Rubber modifier, SMA, ITS, ITM, UCS